Extremal optimization : fundamentals, algorithms, and applications /: fundamentals, algorithms, and applications. (2018) - Lü, Yongzai; Chen, Yu-Wang; Chen, Min-Rong; (Optimization specialist), Chen, Peng; Zeng, Guo-Qiang
No abstract available